PHENOTYPIC DIVERSITY OF RICE GERMPLASM FOR YIELD TRAITS UNDER AEROBIC CULTIVATION - T. RAMESH, A. MALIHA, M. BALRAM, CH. V. DURGA RANI, Y. CHANDRA MOHAN and (The Journal of Research, PJTSAU, 2020)
Rice is central in the food consumption of more than half of global population and also holds a very major share in water used for agriculture. The rapid depletion of water resources is making it a difficult task for the farmers to cultivate rice under flooded condition thus emphasizing the need to shift to aerobic cultivation. As the genetic basis of material suitable for aerobic cultivation is narrow, the present study aims at understanding the performance of germplasm collected from various parts of country under aerobic cultivation. In the present study, one hundred and ten germplasm lines collected from Cuttack, Tamilnadu, Andhra Pradesh, Telangana and Karnataka were evaluated for two seasons. Data was collected on ten yield attributing traits viz., seedling vigour index, days to 50% flowering, plant height, panicle length, total tillers per plant, productive tillers per plant, filled grains per panicle,thousand grain weight, percentage spikelet fertility and grain yield per plant. The results revealed that a significant number of lines had values with desirable range for each trait. Correlation analysis revealed a significant positive correlation between the traits such as productive tillers and thousand grain weight (0.74), plant height with panicle length (0.73) and seedling vigour index (0.56) and panicle length and filled grains per panicle (0.55). The diversity analysis resulted in two major clusters (I and II) with 63 and 47 lines respectively, which further branched into two sub-clusters each (Ia, Ib and IIa, IIb). The cluster I predominantly had lines from Tamilnadu, Andhra Pradesh, Telangana and Karnataka and four national checks for water stress tolerance, while cluster II was dominated by germplasm collected from Cuttack. The present study thus formed a basis to understand the performance of rice germplasm under aerobic cultivation. Lines with desirable agronomic traits can be chosen from both the clusters and exploited in future research towards aerobic rice breeding.